Implementation of Digital Rights Management in the eBook Collection at Digital Library “X” - Nitzah, Nitzah; Heriyanto, Heriyanto (Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi dan Kearsipan, 2025)
Background: This research is motivated by issues and problems related to copyright infringement, including theft, copying, and the unauthorized distribution of content in libraries. The American Library Association (ALA) developed a technology to control access, track, and limit the use of digital content called Digital Rights Management (DRM). Unfortunately, the research on the implementation of DRM as an effort to protect ebook collections is still limited in Indonesia.Objective: This research aims to analyze the implementation of DRM ebook collection protection as a form of protection for digital content.Methods: A qualitative method with a case study approach. Data collection was carried out through interviews, observation, and document study methods. The data analysis technique used is thematic analysis.Results: The results of the data analysis show that the digital library DRM ebook collection at Digital Library “X” does not meet the technical implementation of DRM. This can be seen from the purpose of holding the digital library itself, namely, to provide collections without limiting access to users, so that the technical implementation of DRM, which includes access, use, and distribution, has not been fulfilled.Conclusion: These results indicate that the Digital Library “X” seeks to protect digital collections by not allowing users to download and copy content from DRM ebook collections. Further research should focus on the research by choosing one of the aspects to answer the DRM challenge in libraries in Indonesia.